Uruguay's income inequality and political regimes during 1981 - 2010 - Verónica Amarante; Marco Colafranceschi; Andrea Vigorito (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2011)
This study assesses the evolution of inequality in Uruguay during 1981-2010, considered as subperiods built on the basis of the main policy regimes observed: extreme right (1981-84), centre-right (1985-89), right (1990-2004), and centre-left (2005-10). Income inequality diminished during the restoration of democracy, but started to grow steadily in the mid-1990s and despite recent redistributive reforms, continued to grow, albeit modestly, until 2007. In 2008 inequality lessened, continuing this trend through 2009 and 2010.Trade liberalization, suppression of centralized wage-setting mechanisms, the drop in minimum wages and the lack of a social protection system oriented to the most deprived households explain the rise in inequality during the last decade. In a context of a stable macroeconomic system, the recent fall in inequality resulted from a reduction in labour income inequality and the introduction of noncontributory public transfers schemes.
Keywords: D31; D63; J21; J24; 330; inequality; Uruguay; transfers; wage-setting mechanisms; returns to education; political regimes; Einkommensverteilung; Politisches System; Öffentliche Sozialleistungen; Uruguay